Public drinking and popular culture in eighteenth-century Paris - Brennan, Thomas Edward (Princeton legacy library, 1988)
Adding a new dimension to the history of mentalites and the study of popular culture, Thomas Brennan reinterprets the culture of the laboring classes in old-regime Paris through the rituals of public drinking in neighborhood taverns. He challenges the conventional depiction of lower-class debauchery and offers a reassessment of popular sociability. Using the records of the Parisian police, he lets the common people describe their own behavior and beliefs. Their testimony places the tavern at the center of working men's social existence. Central to the study is the clash of elite and popular culture as it was articulated in the different attitudes to taverns. The elites saw in taverns the indiscipline and exuberance that they condemned in popular culture. Popular testimony presented public drinking in very different terms. The elaborate rituals surrounding public drinking, its prevalence in popular sociability and recreation, all point to the importance of drink as a medium of social exchange rather than a drugged escape from misery, and to the tavern as a focal point for men's communities. Professor Brennan has elucidated the logic of both elite and popular systems of meaning and found new dignity and coherence in the culture and values of the populace. Originally published in 1988. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.